An Overview of Human Rights Violations Against Racial Discrimination: Case Study of Racism Against Vinicius Jr - Gunawan, Yordan; Azham, Kevin Syahru; Akbar Napitupulu, Ichwan Rizki (Susbtantive Justice International Journal of Law, 2024)
The author’s overarching goal is to analyze the Racial discrimination that remains a significant issue worldwide, leading to severe human rights violations. The problem formulation aims to investigate the prevalence and impact of racial discrimination, using a case study of racism against Vinicius Jr (a professional football player). By examining this specific case, we can gain insight into the broader problem of racial discrimination, explore the challenges individuals face, and assess the efforts made to address this violation of Human Rights. By studying the case of racial discrimination against Vinicius Jr, this research aims to shed light on the broader issue of human rights violations resulting from racial discrimination. The research uses normative legal research, which studies the case approach and collects data from journal articles, books, and websites. The study's outcomes will contribute to a deeper understanding of the challenges individuals like Vinicius Jr face and provide insights into effective strategies to combat racial discrimination in football and society. Ultimately, the research aims to promote equal treatment, inclusivity, and respect for human rights, fostering a more just and equitable environment for all.